The impact of protean career orientation on career planning - Shanthakumary, M.C.M.A.; Velnampy, T. (University of Jaffna, 2020)
The career orientation of the people is one of the decisive determinants of work related outcomes. The career orientation of Sri Lankan is significantly changing forever due to the vicissitudes take place in the world of work. The present study aims to examine the effect of protean career orientation on the career planning of individuals. Conveniently selected 154 academic and non-academic staff from public Higher Education Institutions (HEIs) participated in the study. A self-administrated questionnaire was issued among the respondents. Two hypotheses were developed. Partial Least Squares (PLS) method and independent-sample t-test were used to test the hypotheses. The study found that protean career orientation has a significant direct impact on career planning and there is no statistically significant mean difference between men and women in terms of their career orientation; however, they are significantly different in planning their careers.
Keywords: Academic and non-academic staff; Career planning; Gender; Higher education institutions and protean career orientation